2019
DOI: 10.3171/2018.9.peds17225
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of convection-enhanced delivery of IL13-Pseudomonas toxin in children with diffuse intrinsic pontine glioma

Abstract: OBJECTIVEIn this clinical trial report, the authors analyze safety and infusion distribution of IL13-Pseudomonas exotoxin, an antitumor chimeric molecule, administered via intratumoral convection enhanced delivery (CED) in pediatric patients with diffuse intrinsic pontine glioma (DIPG).METHODSThis was a Phase I single-institution, open-label, dose-escalation, safety and tolerabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 28 publications
0
51
0
Order By: Relevance
“…For example, whereas we used a delivery rate of 1 μl/min, clinically, delivery rates in patients with DIPG have been reported in the range of 5-10 μl/min. 9 Despite this, we believe the trends we report are likely to persist in patients with DIPG, although the most optimal delivery value can only truly be optimized prospectively in a clinical trial.…”
Section: Figmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, whereas we used a delivery rate of 1 μl/min, clinically, delivery rates in patients with DIPG have been reported in the range of 5-10 μl/min. 9 Despite this, we believe the trends we report are likely to persist in patients with DIPG, although the most optimal delivery value can only truly be optimized prospectively in a clinical trial.…”
Section: Figmentioning
confidence: 84%
“…3 Interstitial infusion by CED to the brainstem has been proven safe and feasible in multiple animal models, and recently a phase I clinical trial in children with DIPG validated this as safe in human patients. 9,17,19,23,28,31 Post hoc analyses after CED have demonstrated that therapeutic agents achieve high concentrations in the regional parenchyma and adjacent white matter tracts, with negligible efflux in the presence of an intact BBB. 6,7,22,32 Other interstitial infusion approaches distribute infusate by other mechanisms, including osmotic pump delivery, which relies solely on osmotic gradients after catheter insertion to encourage distribution within the target tissue.…”
mentioning
confidence: 99%
“…Therefore, the understanding acquired from adults was applied to children suffering from the disease. However, although treatments for high-grade glioma have achieved modest improvements in survival rates in adults, in children these treatments did not make any difference [ 103 , 104 ]. In 2012, two groups—Schwartzentruber et al and Lindroth et al—showed that mutations in genes that encode histones, the spool-like proteins around which DNA is wound, contribute to high-grade glioma [ 105 , 106 ].…”
Section: Potential Role Of Aptamers In Pediatric Neuro-oncologymentioning
confidence: 99%
“…14 Clinical trials would soon follow that aimed to more concretely assess safety and define infusion parameters by using a systematic dose-escalation format. 4,6,30 Our group was able to report comprehensively that CED in the brainstem of children with DIPG is a rational and reasonably safe treatment option. Twenty-eight patients were enrolled into a phase 1 clinical trial (registration no.…”
Section: Enhanced Drug Deliverymentioning
confidence: 99%